Seizure-induced hilar ectopic granule cells in the adult dentate gyrus - Kasahara, Yuka; Nakashima, Hideyuki; Nakashima, Kinichi (Frontiers in Neuroscience, 2023)
Epilepsy is a chronic neurological disorder characterized by hypersynchronous spontaneous recurrent seizures, and affects approximately 50 million people worldwide. Cumulative evidence has revealed that epileptogenic insult temporarily increases neurogenesis in the hippocampus; however, a fraction of the newly generated neurons are integrated abnormally into the existing neural circuits. The abnormal neurogenesis, including ectopic localization of newborn neurons in the hilus, formation of abnormal basal dendrites, and disorganization of the apical dendrites, rewires hippocampal neural networks and leads to the development of spontaneous seizures. The central roles of ectopic hilar granule cells in regulating hippocampal excitability have been suggested. In this review, we introduce recent findings about the migration of newborn granule cells to the dentate hilus after seizures and the roles of seizure-induced ectopic granule cells in the epileptic brain. In addition, we delineate possible intrinsic and extrinsic mechanisms underlying this abnormality. Finally, we suggest that the regulation of seizure-induced ectopic cells can be a promising target for epilepsy therapy and provide perspectives on future research directions.